Case reportSweet’s syndrome with idiopathic thrombocythemia - Kaszewski, Sebastian; Czajkowski, Rafał; Protas-Drozd, Franciszka; Placek, Waldemar; Jakubowski, Sebastian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Diagnosis of paraneoplastic skin syndromes associating neoplastic processes is assumed as the crucial aspect of dermatological practice. Knowledge of clinical findings of dermatoses suggesting coincidence of malignant proliferative processes facilitates diagnostic and therapeutic procedures. We would like to present a case of Sweet’s syndrome, qualified for comparative paraneoplastic skin syndromes. Sweet’s syndrome, acute, febrile neutrophilic dermatosis, was first described by Robert Douglas Sweet in 1964 as a disorder characterized by fever, skin lesions of erythematous-infiltrative character, leukocytosis with neutrophilia and dense infiltrations of dermis by mature neutrophils. Sweet’s syndrome aetiology is not fully understood, although cytokine abnormalities suggest that Th1 lymphocytes play an important role in pathogenesis of the dermatosis. Factors inducing Sweet’s syndrome include: haematopoietic hyperplasia; neoplasms: genitourinary, breast, gastrointestinal; infections of the respiratory and alimentary system; inflammatory bowel diseases; drugs; pregnancy and vaccinations. Systemic corticosteroids are the “gold standard” of Sweet’s syndrome treatment; potassium iodide or colchicine may also be used. Indomethacin, clofazimine, cyclosporine A and sulfones are the second-line drugs.